SHARIAH STOCK EXCHANGE IN ISLAMIC CONFERENCE ORGANIZATION MEMBERS (OIC) IS THERE ANY INTEGRATION? - Indo Yama Nasarudin; Deni Pandu Nugraha; Bisri , (Fakultas Ekonomi dan Bisnis Islam, 2021)
This research examines the integration of the Indonesian Islamic Stock Exchange with the Islamic stock exchange in five OIC member countries. In particular ways, Malaysia, Pakistan, Kuwait, Turkey, and Qatar. This order was picked dependent on the world income grouping of the Organization of Islamic Cooperation (OIC). This investigation applies the technique for Vector Autoregressive (VAR)/Vector Error Correction Model (VECM) and day by day, shutting records information spreading over from 2013 to 2018. The outcomes show no causality connections among all Islamic stock exchanges in Malaysia, Pakistan, Kuwait, Turkey, and Qatar, with the Indonesian Islamic stock exchange. Based on cointegration analysis, Malaysia's Islamic stock exchange has a long-term relationship with the Indonesian Islamic stock exchange Indonesia. Furthermore, based on variance decomposition (VD) analysis, Indonesia's Islamic stock market provides the most significant contribution to the Islamic stock market of Pakistan's movement.